Stem Cell-Derived Nanovesicles: A Novel Cell-Free Therapy for Wound Healing - Jianghong Huang; Jun Zhang; Jianyi Xiong; Shuqing Sun; Jiang Xia; Lei Yang; Yujie Liang (Hindawi Limited, 2021)
Wound healing and regeneration are a dynamic and complex process that requires a collaborative effort between growth factors, epidermal cells, dermal cells, extracellular matrix, and vessels local to the wound area. Mesenchymal stem cells participate in the recruitment site, mainly by releasing secretory factors and matrix proteins to promote wound healing. Stem cell-derived nanovesicles (CDNs), including microvesicles, exosomes, and exosome mimetics, contain most of the biologically active substances of their parent cells and have similar effects. CDNs can shuttle various proteins, messenger RNAs, and microRNAs to regulate the activity of receptor cells, and they play important roles in skin wound healing. This article reviews recent research progress on CDNs for wound repair. We summarize current knowledge on how CDNs regulate immunity, fibroblast activity, angiogenesis, and scar formation in the wound healing process. This review can help researchers explore new treatment strategies to enhance the therapeutic efficacy of CDNs, which have a promising future as naturally cell-free therapies.